2002
DOI: 10.1111/j.1550-7408.2002.tb00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Host and Parasite‐Derived Cellular and Extracellular Matrix Components in Developing Cysts of Myxobolus pendula (Myxozoa)

Abstract: Cysts of Myxobolus pendula from the gill arch of creek chub (Semotilus atromaculatus) were examined at various stages of development using light and electron microscopy. The subepithelial host connective tissue underwent dramatic changes, including degradation and remodelling of collagen and vascularisation, in response to the infection. Inflammatory cells lay in a fluid-filled space beneath the host's connective tissue and surrounded a distinctive parasite-derived matrix, composed of collagen fibril bundles e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…This finding is in line with former reports (Adriano et al 2005, Zhang et al 2010. Manera (2016) indicated that fibroblast and collagen encapsulation of plasmodia may protect the parasite against external influences whereas Martyn et al (2002) mentioned that the complexity is probably selectively permeable for nourishing the parasite. The derivation and function of cup-like cells observed here merited a further study to elucidate the host-parasite interaction mechanism.…”
Section: Histopathological Examinationsupporting
confidence: 82%
“…This finding is in line with former reports (Adriano et al 2005, Zhang et al 2010. Manera (2016) indicated that fibroblast and collagen encapsulation of plasmodia may protect the parasite against external influences whereas Martyn et al (2002) mentioned that the complexity is probably selectively permeable for nourishing the parasite. The derivation and function of cup-like cells observed here merited a further study to elucidate the host-parasite interaction mechanism.…”
Section: Histopathological Examinationsupporting
confidence: 82%
“…Some examples of cellular innate responses to piscine myxosporeans are documented, such as the neutrophil and eosinophil-like infiltration during gill inflammation in channel catfish infected with Henneguya spp., whose degranulation within lesions was associated with further host tissue damage (Lovy et al 2011). Furthermore, the time-dependent succession of granulocytes and lymphocytes in the oedemata surrounding Myxobolus pendula branchial cysts was described in creek chub (Martyn et al 2002). Other studies on leukocyte contribution during piscine parasitoses involve tapeworms and acanthocephalans (Dezfuli et al 2011a(Dezfuli et al , b, 2012a(Dezfuli et al , c, 2013Hansen et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The parasitic worm Schistosoma mansoni Sambon, 1907 has been shown to acquire an extensive range of host antigens that are subsequently expressed on the parasite tegument (Abath & Werkhauser 1996). Study of the development of the myxozoan parasite Myxobolus pendula Guilford, 1966 has shown an association of the growth of parasitederived cysts with degradation of host connective tissue and remodelling of fibrillar collagen (Martyn et al 2002). These authors compared and contrasted the morphology of host and parasitic collagen fibres, and suggested that host material was reorganised during cyst development.…”
mentioning
confidence: 99%